Multiple Sclerosis and Related Disorders - Goodin, Douglas S.; ScienceDirect eBooks (Amsterdam : Elsevier Science, 2014)
Multiple Sclerosis (MS) is generally understood to be an inflammatory autoimmune disease of the central nervous system. While we still are not certain of the root cause of MS, research results suggest that unknown environmental factors and the presence of specific genes seem the most probable targets. MS causes an inflammatory response in the central nervous system leading to neurodegeneration, oligodendrocyte death, axonal damage, and gliosis. Over the past five years ongoing research has greatly expanded our understanding of the pathogenesis of MS, detailed insight into the epidemiology and genetic factors related to MS, the introduction of new technologies and tests to better diagnose and predict the future course of the disease and the introduction of new treatments targeting MS. This collection of review chapters provides a comprehensive reference into the science and clinical applications of the latest Multiple Sclerosis research and will be a valuable resource for the neuroscience research community and the clinical neurology community of researchers and practitioners.
Section 1: Pathogenesis -- Section 2: Epidemiology and genetics -- Section 3: Diagnosis and disease course -- Section 4: Treatment -- Section 5: Other demyelinating diseases -- Section 6: Capita selecta.
Print version record.
Elsevier
Keywords: Multiple sclerosis; Multiple sclerosis -- Treatment; Neurology; Central nervous system -- Diseases -- Periodicals; Multiple sclerosis -- Periodicals; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Central nervous system -- Diseases; Multiple sclerosis; Multiple sclerosis -- Treatment; Neurology; Multiple Sclerosis; Central Nervous System Diseases; Electronic books